Fasilitasi Kemajuan Kebudayaan melalui Fotografi Lubang Jarum Sebagai Media Edukasi Anak - Muhammad Roestian Fahmi Nasution; Nora Anisa Br Sinulingga; Julia Hidayah Nasution; Hafiz Arham; Via Esterlina Br Ginting (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The Cultural Advancement Facilitation through Pinhole Photography as an Educational Medium for Children program aims to enhance cultural literacy, creativity, and awareness among young generations regarding the preservation of Malay Deli cultural heritage. This initiative is motivated by the declining interest of children in local history and culture amid rapid modernization, particularly in coastal areas with limited access to educational resources. Pinhole photography is employed as an educational approach due to its simplicity and reflective nature, fostering patience, accuracy, and a fundamental understanding of the interconnection between art, science, and culture. The program was conducted over three days through a series of activities, including workshops on constructing pinhole cameras, field exploration and photography at Malay Deli heritage sites namely Maimun Palace, Al- Mashun Grand Mosque, Al-Osmani Grand Mosque, and Sri Deli Park and photo developing and curation sessions. The activities actively involved children from the Rumah Edukasi Anak Pesisir community as primary participants in the visual documentation of cultural heritage. The results indicate an improvement in participants’ understanding of Malay Deli historical and cultural values, the development of creative and reflective thinking skills, and the production of children’s photographic works with potential use as educational and cultural promotion media. Overall, this program contributes to participatory-based cultural advancement and strengthens sustainable cultural tourism through an educational, creative, and sustainable approach.